KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK PRIBADI DI KPP SEMARANG TENGAH II (Students' Journal of Accounting and Banking, 2013)
Government efforts to increase domestic revenues from the tax sector, among others, by changing the system of tax collection from the official assessment system to self assess-ment system was implemented. Self assessment is a tax collection system that authorizes the taxpayer to determine the amount of tax payable. The purpose of this study was to analyze the factors that affect personal tax compliance of taxpayers. This study used a sample of 90 respondents using accidental sampling method, the individual taxpayer who performs registered in the KPP Semarang Tengah II. The collection of the data used in this study is a questionnaire. Data analysis was performed using multiple linear regression analysis with SPSS 16.00. The results of this study indicate that the clarity of laws and tax regulations, the level of education and the perception of taxpayers significant effect on tax compliance.Keywords: clarity of laws and taxation regulations, education, perception of taxpayers against tax officials, tax compliance.